One Size Fits All Learning Preferences: an Exploration of Rapid Authoring Tools - Niav McEvoy (Irish Journal of Academic Practice, 2013)
Virtual Learning Environments (VLEs) are increasingly being used by colleges and universities to deliver and/or complement traditional face-to-face courses. The range of learning technologies available for use within these virtual platforms is considerable, but how confident are we that these learning tools support the learning process for students? It is crucial that the learning tools utilised in virtual platforms do not cause additional barriers for the online and distant learner. This Survey research study is designed to determine if rapid authoring tools can meet the needs of a variety of learning preferences of adult learners. The study focuses specifically on the use of virtual tutorials, created using the rapid authoring tool Articulate Presenter 2007, to establish the learning preferences of the students as represented by Fleming's (2011) VARK model. In total, ten variations of the VARK learning preferences were represented across respondents, with the majority indicating a uni-modal preference in an online self-administered questionnaire. Overall, the majority of students responded positively in relation to their experience of the virtual tutorial.